Analysis of the Effect of Return on Equity, Debt-to-equity, Net Profit Margin on Price-to-earnings Ratio - Supriono, Supriono (Economic and Business Horizon, 2022)
The current research was aimed at analyzing the impact of Return on Equity, Debt-to-equity, and Net Profit Margin simultaneously as well as partial effects, and to empirically find out which variables have a higher contribution to the Price-to-earnings ratio in the Property and Real Estate Companies listed in Indonesia Stock Exchange. All properties and real estate companies that go public and are listed at IDX were taken as the population, which ranges from 2009 to 2012, and those companies have published the reports periodically as consideration. Meanwhile, the purposive sampling method was deployed, and the present study used 34 companies as a sample. The statistical output demonstrated that Return on Equity, Debt-to-equity, and Net Profit Margin significantly affect the Price-to-earnings ratio. Meanwhile, in a partial test conducted among variables, the finding showed that Return on Equity and Debt-to-equity were insignificant on the Price-to-earnings ratio, while Net Profit Margin has a significant effect on the Price-to-earnings ratio.